Exploring intersectional inequalities in students' sense of belonging in education across educational pathways and across educational contexts - Kleemola, Katri; Toom, Auli; Hyytinen, Heidi; Tuononen, Tarja; Karacay, Irem; Kroezen, Taylor; Kogan, Irena; Alieva, Aigul (Frontiers in Education, 2025)
IntroductionThe study investigated inequalities in the sense of belonging in education among students in primary, secondary and tertiary levels in various European, North American and Oceanian countries. Variation across different educational contexts was explored by examining example countries (Finland, Hungary and Ireland). An intersectional approach to inequalities was adopted; more specifically, an intersection between gender, migration and socioeconomic status was emphasized. The focus of the study was the sense of belonging in education among students representing different intersectional groups in different stages of the educational pathway across educational contexts.MethodData from the PIRLS, TIMMS, PISA, and Eurostudent were harmonized and analyzed. In addition, macro-level indicators characterizing educational policies and practices were used to pinpoint different educational contexts. Regression analysis was used to explore inequalities in the sense of belonging.FindingsOur results demonstrate the extensive complexity of sense of belonging in education on an individual level, and various dynamics across intersectional groups as and educational stages. Across all educational stages native females with high socioeconomic status had the strongest sense of belonging.DiscussionOur results also show that characteristics of macro-level educational contexts have multifaceted and even contradictory associations with inequalities in students' sense of belonging in education.